Mechanical Punctate Pain Thresholds in Patients With Migraine Across Different Migraine Phases: A Narrative Review - Pan, Li-Ling Hope; Treede, Rolf-Detlef; Wang, Shuu-Jiun (Frontiers in Neurology, 2022)
Purpose of the review We reviewed the studies of mechanical punctate pain thresholds (MPTs) in patients with migraine and summarized their findings focusing on the differences in MPT measurement and MPTs in different phases of migraine. Methods We searched the English-written articles that investigate the MPTs in the migraine population published in peer-reviewed journals with full-text using the PubMed, Web of Science, and Google Scholar databases. Moreover, we manually searched the references from the articles for possibly related studies. Main findings We collected 276 articles and finally included twelve studies in this review. Most of the studies that included MPTs were measured with traditional von Frey filaments. The cephalic areas were always included in the assessment. Most studies compared the inter-ictal MPT in patients with migraine to controls. Among them, the majority found no significant differences; however, there were studies found either higher or lower levels of MPTs in migraine. Even though the studies provided the criteria to define the inter-ictal phase, not all of them followed up with the subjects regarding the next migraine attack. In studies that compared MPT between phases, lower MPTs were found during peri-ictal phases. Summary Changes to MPT in migraine patients were inconclusive. The selection of measurement